Equity retirement and other determinants impact on return on equity in US local farm supply and grain marketing cooperatives - Stander, Christina Ruberson (Kansas State University, 2021)
The environment surrounding cooperatives is evolving and becoming more challenging due to financial concerns stemming from a turbulent agricultural economy, trade uncertainty, and the need to update infrastructure. In addition, cooperatives are financed differently than typical agribusinesses which makes financial decision making even more challenging. To remain competitive and successful in profitability, cooperatives need to operate with efficient assets and sound financial decisions regarding investments, business dealings, and equity. This study analyzes the profitability of cooperatives utilizing 5 different regression models. The first model uses more current cooperative data to update the article by Boyd, Boland, Dhuyvetter, and Barton (2007), which focuses on the financial ratios and performance measures of current ratio (CR), assets-to-equity (ATE), lagged return on equity (ROE), net profit margin (NPM), asset turnover (AT), times-interest-earned (TIE), risk, and total assets (Assets) and their impact on ROE. Four additional models are used in this study to explore the relationship between retiring equity back to patrons and ROE. The added variables are equity retirement as reported by cooperatives, a state interaction term which is a dummy variable that is set to 1 if a state has a law requiring equity retirement upon death of the member. The results find there are four statistically significant variables at the .10 level in all the models that impact future ROE which are lagged inverted current ratio (CRinv), lagged Assets-to-equity (ATE), lagged ROE, and lagged Net Profit Margin (NPM). The results between Boyd et al. and this study are results in relation to the profitability ratios and liquidity ratios. Lagged ROE and NPM are the profitability variables that impact future ROE in a positive manner as do lower levels of liquidity demonstrated by the variable CRinv. A difference from Boyd et al. (2007) is the result that higher leverage ratios demonstrated by ATE, are correlated with an increase in future profitability. This difference warrants additional research to discover the potential reason. Equity retirement was shown to have no effect on future ROE. However, adding “net” allocated equity corresponds with higher future profitability. The analysis found that cooperatives within states with legislation requiring them to retire equity would have lower future ROE, on average, than cooperatives in states with no legislation.
Keywords: Agricultural economics; Cooperatives; Finance; Equity retirement